PCOS: a raising problem; due to recent trends - Selvi Arumuga Nainar, Anitha Thamarai; Loganathan, Malarvizhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovaries with its symptom complexes (PCOS) constitute about 30% of the cases seen every day in patients coming for scan in our hospital. Since PCOS is associated with various long-term complications it is important to analyze is its incidence and its cause for the increase. Methods: The study included 600 women who came for USG for various complaints who had USG features of PCO. Their symptoms, marital and obstetric history was recorded their general appearance and BMI were also recorded and analysed. Their food pattern and physical activity was also elicited. Results: PCO was a finding in around 24% of unwed teenage girls. PCO affected both obese (21.4%) and non-obese (56.2%) women. The complaints for which they come were mainly menstrual disturbances and primary (28.8%) infertility and secondary (22.6%) infertility. Conclusions: Early identification of PCO is essential and its treatment will prevent various long-term complications of it in the future generation.